2013
DOI: 10.1038/ncomms3005
|View full text |Cite
|
Sign up to set email alerts
|

Myosin Vb controls biogenesis of post-Golgi Rab10 carriers during axon development

Abstract: Polarized membrane addition is crucial for axon development and elongation during neuronal morphogenesis. This process is believed to be regulated by directed membrane trafficking of Rab10-containing post-Golgi carriers. However, the mechanisms underlying the biogenesis of these carriers remain unclear. Here, we report that Rab10 interaction with myosin Vb (MYO5B) determines the formation of Rab10 carriers and is important for axon development. Rab10 interacts with the exon D-encoded domain of MYO5B. Downregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 61 publications
4
63
1
Order By: Relevance
“…Rab10 is also reported to be necessary for axonal membrane trafficking and axonal elongation (Wang et al, 2011b;Liu et al, 2013). Rab13, a Rab closely related to Rab8 and Rab10, is reported to be necessary for neurite elongation (Sakane et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Rab10 is also reported to be necessary for axonal membrane trafficking and axonal elongation (Wang et al, 2011b;Liu et al, 2013). Rab13, a Rab closely related to Rab8 and Rab10, is reported to be necessary for neurite elongation (Sakane et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that Rab10 is associated with PPVs [24], Myosin V controls biogenesis of postGolgi Rab10 carriers [27], and JIP1 mediates anterograde transport of Rab10-PPVs during axon development [56]. How do Rab10 vesicles dock and fuse with the membrane at the destination sites?…”
Section: Discussionmentioning
confidence: 99%
“…In addition to several known Rab10-binding partners, such as AS160, a GTPase-activating protein (GAP) for Rab10 [25], or Myosin V [26,27], we also identified MARCKS as one of the interesting hits. Indeed, both MARCKS and Rab10 were expressed in the rat brain at early or late developmental stages (Figure 1A).…”
Section: Rab10 Binds To Marcks Through Effector Domainmentioning
confidence: 99%
See 2 more Smart Citations